Modelling copper smelting – the flash smelting plant, process and equipment. Issue 2 (2nd April 2020) - Taskinen, Pekka; Jokilaakso, Ari; Lindberg, Daniel; Xia, Jiliang
ABSTRACT: The effectivity of present copper smelting technologies have their roots in industrial and laboratory-scale experience accumulated over the past decades. Since early '60s, the tools for improving the processing conditions and smelting vessel design included scale modelling and manual computing of homogeneous multicomponent equilibria. The scale models were isothermal, room temperature constructions where water or air was used as medium and dimensionless numbers ensured scale down and scale up similarities. Today, numerical modelling has opened new insight into the high temperature process modelling where chemical reactions and their heat sinks and sources can be included in the simulations. The utilisation of computational thermodynamics enables a rigorous management of the phase equilibria in industrial multi-components slag-matte-metal systems. This development will be visualised in the framework of various enabling techniques.